PEMBUATAN DENTAL RECORD YANG BAIK: IDENTIFIKASI IMIGRAN KORBAN KAPAL TENGGELAM DI TRENGGALEK 2011 - Novita, Masniari; Noegroho, Waloejo (STOMATOGNATIC- Jurnal Kedokteran Gigi, 2013)
The main purpose of forensic identification is to match the Ante Mortem (AM) data to the Post Mortem (PM) data. In the DVI operation dental identification is one of the primer identifiers including finger prints and DNA. The most crucial problem is when the AM data is not sufficient enough to be compared with the PM data. Objectives. To compare the identification of immigrant victims in Trenggalek case and victims of Senopati case through the prosthetic aspect. Case Operation Procedure. From 103 victims of Trenggalek case only 49 victims were identified from medical, dental, property, fingerprint and DNA. Only 12 were identified by dental. There were 5 victims using porcelain bridge but none of them were identified by the prosthetic work. Compared with the Senopati case, 1 victim was identified from the partial denture worn. Conclusions. Forensic odontology identification depend on a good dental record made by a dentist as a AM data, and compared with the PM data from the victims. Prosthetic work is one of the good dental identifier because it has a spesific characteristic such as the cast, denture outline, material and number of teeth. There should be a good dental record from the prosthetic work that could be used as the AM data.